Aristotle on multiple demonstration. Issue 5 (3rd September 2019) - Comay del Junco, Elena
ABSTRACT: How many scientific demonstrations can a single phenomenon have? This paper argues that, according to Aristotle's theory of scientific knowledge as laid out in the Posterior Analytics, a single conclusion may be demonstrated via more than one explanatory middle term. I also argue that this model of multiple demonstration is put into practice in the biological writings. This paper thereby accomplishes two related goals: it clarifies certain relatively obscure passages of the Posterior Analytics and uses them to show how Aristotle explains biological phenomena by reference to both final and material causes in the Parts of Animals . The first part of the paper explains the account of multiple demonstration present in the Posterior Analytics and distinguishes it from another kind of plural explanation rejected by Aristotle. The second part of the paper turns to the biological explanation in the Parts of Animals and shows how Aristotle's account of multiple demonstrations works in practice. The paper thus provides evidence for the claim that the 'applied' reasoning on display in the biological works is in harmony with the framework of the logical treatises, and thus may also shed light on questions of the unity of the Aristotelian corpus.